2022
DOI: 10.1108/jima-01-2022-0001
|View full text |Cite
|
Sign up to set email alerts
|

AI-enabled technologies to assist Muslim tourists in Halal-friendly tourism

Abstract: Purpose This paper aims to present a theoretical account of the connection between artificial intelligence (AI) enabled technologies and Muslim-friendly tourism experiences (MFTX) using the customer experience (CX) theory, reference group theory and theory of tourism consumption systems. Design/methodology/approach A model research design is adopted to build a theoretical framework that predicts relationships between constructs. Critical assessment in tourism and AI literature is used to explore AI-enabled t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 103 publications
0
17
0
1
Order By: Relevance
“…In terms of Muslim travel, behavioural intention has been discussed in the context of visiting Muslim countries (Kim et al, 2015;Lestari et al, 2022), non-Muslim countries (Aji et al, 2020;Wibawa et al, 2021) and in general (Papastathopoulos et al, 2020;Rahman et al, 2020). The findings have shown that there are many factors driving Muslim consumers to choose certain travel destinations, whether directly or indirectly, such as destination image (Battour et al, 2010b;Lestari et al, 2022), motivation , technology (Battour et al, 2022;Berakon et al, 2023), religiosity (Eid and El-Gohary, 2015a;Sudarsono et al, 2021), knowledge (Sudarsono et al, 2021) or halal considerations (Wibawa et al, 2021). Aji (2017) argued that scepticism would lead to a negative attitude towards halal products, which leads to a decreased purchase likelihood.…”
Section: Intention To Engage In Muslim-friendly Travelmentioning
confidence: 99%
“…In terms of Muslim travel, behavioural intention has been discussed in the context of visiting Muslim countries (Kim et al, 2015;Lestari et al, 2022), non-Muslim countries (Aji et al, 2020;Wibawa et al, 2021) and in general (Papastathopoulos et al, 2020;Rahman et al, 2020). The findings have shown that there are many factors driving Muslim consumers to choose certain travel destinations, whether directly or indirectly, such as destination image (Battour et al, 2010b;Lestari et al, 2022), motivation , technology (Battour et al, 2022;Berakon et al, 2023), religiosity (Eid and El-Gohary, 2015a;Sudarsono et al, 2021), knowledge (Sudarsono et al, 2021) or halal considerations (Wibawa et al, 2021). Aji (2017) argued that scepticism would lead to a negative attitude towards halal products, which leads to a decreased purchase likelihood.…”
Section: Intention To Engage In Muslim-friendly Travelmentioning
confidence: 99%
“…information processing and dissemination about swimming pools, food and place of worship) in accordance with the Shariah obligations (Razak et al , 2019; Moshin et al , 2020). Besides, Battour et al (2022) define halal services as the information books or guidebooks that contain the necessary particulars and guidance, including halal food, halal swimming pools and spa, halal gymnasium, place of worship and airports. The current study evaluates the halal services in terms of designations’ information, containing in flyers and brochures, and in languages such as Bangla, English and Arabic, which are conformed to Islamic laws.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ratnasari et al (2021) have observed that halal certification and halal logos impact behavioral intentions toward halal tourism. Further, halal tourism attributes, such as Islamic dress code (Fajriyati et al , 2020), prayer time and halal entertainment (Battour et al , 2022) and tourists’ emotional bonds (Battour et al , 2022), impact intentions toward halal tourism. Thus, the debate still exists in the literature about what attributes dominantly influence tourists’ behavioral intentions toward halal tourism.…”
Section: Introductionmentioning
confidence: 99%
“…İşletmelerin rekabet üstünlüğü elde edebilmek için teknolojik açıdan da ön planda olmaları gerekmektedir. Turizm işletmeleri teknolojik olarak her daim otomasyon sistemleri ve robotik sistemlere önem vermeleri gerekmektedir (Battour, 2022a). Bu sayede işletmeler helal turizm pazarında kendileri var olabilecek ve varlıklarını daha kolay sürdürebileceklerdir.…”
Section: Müslüman-dostu Teknolojik Uygulamalarunclassified